Social justice counseling : the next steps beyond multiculturalism - Chung, Rita Chi-Ying.; Bemak, Fred. (Thousand Oaks, Calif. : SAGE Publications, 2012)
'Social Justice Counseling is the next step toward alleviating the injustices faced by individuals in society and it is a natural extension of multicultural counseling. Issues of social justice are dominating conferences across the mental health disciplines, with a greater focus on alleviating broader social inequities such as equity, access and fairness for each individual. At a micro level social justice issues play out in the form of gender discrimination, sexual harassment, equal access to education, fair housing, and more. Traditionally counselors have been focused on the individual, however, in recent years there has been a shift for all mental health professionals to address issues of social class, race and ethnicity and more. This books offers a supplement to important issues regarding social justice and will highly enhance the content taught in multicultural courses. The authors are leading authorities on social justice counseling and have led the way to create a specialization in social justice counseling at their school at George Mason University. This book is the first to bring all these concepts together, tie them to multiculturalism, and offer personal applications and tools for mental health professionals. It is theoretical yet highly practical in offering concrete steps toward becoming more social justice oriented'--Provided by publisher.
'This book offers a supplement for courses on diversity and multicultural counseling to important issues regarding social justice and will highly enhance the content taught in terms of broader social justice issues. The authors are leading authorities on social justice counseling and have led the way to create a specialization in social justice counseling at their school at George Mason University. This book is the first to bring all these concepts together, tie them to multiculturalism, and offer personal applications and tools for mental health professionals. It is theoretical yet highly practical in offering concrete steps toward becoming more social justice oriented. It offers an outline of how social justice fits into the larger context of psychology and mental health and is intended for counseling, social work and psychology graduate level students. It's goal is to help faculty help students take action and challenge them to work on a broader systemic level to combat issues of discrimination and inequity'--Provided by publisher.
Machine generated contents note: Part I: Introduction to Counseling and Social Justice1. Introduction2. Theories of Multicultural Counseling3. Theories of Social JusticePart II: Multi-Level Model of Psychotherapy, Counseling, Social Justice and Human Rights4. Development and Rationale for the Multi-Level Model of Psychotherapy, Counseling, Social Justice and Human Rights5. Multi-Level Model of Psychotherapy, Counseling, Social Justice and Human RightsPart III: Social Justice Journeys and Personal Applications6. The Journey of an Asian Human Rights and Social Justice Road Warrior: Rita Chi-Ying Chung7. Ther Personal Journey of a Social Justice and Human Rights Advocate: Fred Bemak8. Social Justice Reflections of Graduate StudentsPart IV: Critical Social Justice Tools9. Change Models10. Leadership and Social Justice11. Advocacy and Social Justice12. Myths and Realities of Empowerment13. Interdisciplinary Collaboration as a Means Towards Social JusticePart V: Social Justice Applications14. Social Action Research and Social Justice15. Model Higher Education Programs in Social JusticePart VI: Social Justice in a Global World16. Social Justice in a Global World17. Conclusion.
Includes bibliographical references and index.
Keywords: Cross-cultural counseling; Psychiatry, Transcultural; Social justice